PROFIL KEBUGARAN ATLET FUTSAL KABUPATEN KLATEN DINYATAKAN DENGAN VO2MAX - Agung Widodo; Bachtiar Bachtiar; Sayid Fariz; Yunensy Novitasari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Futsal is a team sport that relies on high-intensity intermittent activity that requires athletes with excellent physical fitness. Optimal fitness conditions (VO2Max) are the main capital for every futsal athlete so they can concentrate fully and work optimally from the start to the end of the match. The purpose of this study was to find out how the fitness profile (VO2Max) of 14 futsal athletes in Klaten Regency was prepared to face the 2022 Central Java PORPROV event. This study used a quantitative descriptive approach with a survey method. Fitness data collection instrument with tests and measurements with the Multistage Fitness Test (MFT). The main finding in this study is the fitness level (VO2Max) of the Klaten Regency futsal athletes as much as 42.87% is at a moderate level, 42.85% is at a less and less level, and only 14.28% is at a good level. Seeing these findings, it means that the fitness condition of the majority of Klaten Regency futsal athletes is at a moderate level. The results of this study are expected to provide benefits as a scientific basis for increasing athletes' VO2Max so that it has an impact on increasing performance which results in achieving maximum performance.